Implementation of the Regional Regulation of Palembang City Number 03 of 2017 Concerning the Establishment of RT / RW (Study of Plaju Village, Plaju District) - Pratiwi, Winda Aulia; Alfatih, Andy (HM Publisher, 2019)
each RT not according to the capacity regulated in Palembang City Regulation No. 03 Year 2007 chapter III article 4 paragraph 1, and also the number of RTs and RWs is not in accordance with the minimum and maximum limits set in Palembang City Regional Regulation No. 03 Year 2007 chapter III article 4 paragraph 2. While the type of this research is quantitative descriptive research type. This research was conducted with a population of 61 respondents, namely RT and RW in Plaju Ulu Sub-District, Plaju City, Palembang, and was conducted between May and October 2018. And the method of data collection was completed by distributing questionnaires, observations and structured interviews. From the results of the study it was found that the level of compliance and smoothness of Palembang City Government Regulation No. 03 year 2007 regarding the formation of RT / RW was considered quite successful. However, the performance and impact of Palembang City Government Regulation No. 03 Year 2007 regarding the formation of RT / RW was still in the category of unsuccessful. Nevertheless, it can be concluded that the Implementation of Palembang City Government Regulation No. 03 year 2007 regarding the formation of RT / RW has been carried out quite successfully.